O processo de leitura hiperficcional: um estudo de caso em A dama de espadas - Santos, Marcelo da Silva Araújo (2009)
This work develops a case study of a prominent narrative experiment that arises from the application of hypertext in the field of fiction, called hyperfiction, in order to describe and analyze the process of reading this kind of fictional expression, consisting of micronarratives, that does not have a reading order pre-established and not a predetermined outcome. We outlined the precepts that govern the operation of the hypertext, noting its features are transformed into strategies for the construction of narrative in digital media, so that we can investigate how the elements of the digital affect the act of reading in particular, the fictional text. Our approach provides an overview on the history of hyperfiction considering the evolution of written communication techniques and their relation to reading practices and the influence of certain literary techniques used in the print culture in some of the characteristics of hyperfiction. To perform the study, we chose "A dama de espadas", hyperfiction of the Marcos Palacios and one of the first Brazilian productions of the genre, as a research subject for that from his immersion in the narrative plot we can see how the technical devices of hypertext and its expressive form, characterized by non-linearity, interactivity and presence of visual language and sound are in the structure establish their specific protocols of reading and meaning construction. The goal is to understand how the links, the audiovisual elements and non-linearity stimulate specific procedures for reading and meaning construction. To complement this analysis, we turn to the study of linguistics that deal with the hypertext and reading of literary theories that support the examination of literary production in post-modernity, and we believe strongly supported by the study of hyperfiction, since the concepts of the literary hypertexts are still in the process of formulation.